2023
DOI: 10.3390/en16104072
|View full text |Cite
|
Sign up to set email alerts
|

A Rigorous Standalone Literature Review of Residential Electricity Load Profiles

Abstract: The introduction of smart meters and time-use survey data is helping decision makers to understand the residential electricity consumption behaviour behind load profiles. However, it can be difficult to obtain the actual detailed consumption data due to privacy issues. Synthesising residential electricity consumption profiles may be an alternative way to develop synthetic load profiles that initially starts by reviewing the existing synthetic load profile methods. The purpose of this review is to identify the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 84 publications
(333 reference statements)
0
2
0
Order By: Relevance
“…In addition, collected data can only describe a limited number of evaluation scenarios. Synthetic data generation can bridge these gaps by producing inexpensive, secure, and customizable building electricity load profiles that can describe multiple scenarios [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, collected data can only describe a limited number of evaluation scenarios. Synthetic data generation can bridge these gaps by producing inexpensive, secure, and customizable building electricity load profiles that can describe multiple scenarios [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Probabilistic and physics-based models are usually used for synthetic data generation [7]. Probabilistic models are easier to develop, however they can oversimplify systems.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, research on the modelling and analysis of residential electricity load profiles will contribute to the energy demand in specific areas: neighbourhoods, districts, cities, or regions and, specifically, the CITIES and PEDs research projects. One of the fundamental aims of these projects is to understand residential electricity consumption behaviour by synthesising local load profiles within cities [28,35]. The residential sector is of great importance, as it contributes to approximately 30% of the global demand for electricity [2].…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, load-shifting forms part of our research on DSM in the residential sector (Figure 1). In our previous works on synthesising residential electricity load profiles [28,[35][36][37], we found that appliances are mainly used to synthesize domestic load profiles. In accordance with what was revealed in [15], there is a need to incorporate the consumption patterns of electrical appliances into DSM models.…”
Section: Introductionmentioning
confidence: 99%